Beliefs of Two Culturally Diverse Groups of Teachers About Intercultural Bilingual Education - Fabián Benavides Jimenez; Yenny Lisbeth Mora Acosta (Universidad Nacional de Colombia, 2019)
This article provides an overview of the ideas that two groups of bilingual teachers from different contexts, one indigenous and the other Western, have about the concepts of education, bilingualism, and interculturality. Their opinions were gathered through focus groups, semi-structured interviews, and videos, and reviewed under light of what the theoreticians have pointed out regarding the three mentioned concepts. One important outcome was the enrichment of perspectives of both groups of participants, and a remarkable conclusion that refers to the similar perceptions both groups have regarding the concept of education. Further research should address how each community perceives its own educational model and how it can be complemented with the views of the other.